ANALYSIS OF POTENTIAL INTERACTIONS OF RAMIPRIL -AMBON BANANA (Musa paradisiaca var. sapientum (L.) Kunt.) ON HYPERKALEMIA RISK IN WHITE RATS - Sintia Dewi, I Gusti Ayu; Adi Jaya, Made Krisna; Agristy, Ni Putu Rutin Seciolini; Gendari, Ida Ayu (Journal Pharmaceutical Science and Application; Vol 3 No 2 (2021): Journal Pharmaceutical Science and ApplicationDO - 10.24843/JPSA.2021.v03.i02.p05, 2021)
Introduction : Drug and food interaction is a condition in which nutritional factors present in food have an influence significant effect on drug therapy, both potentially increasing or decreasing the effect of drug therapy. Indonesian people have a habit of taking medicine by using food or drink. Bananas are the primadona that are often consumed to speed up the swallowing process and reduce the bitter taste of medicine. It turns out that the consumption of bananas together with ACE inhibitors can increase the risk of hyperkalemia. Lack of information about the effects caused by drug and food interactions, so it is necessary to do related research.  Objective : This study aims to determine the interaction of giving ramipril together with Ambon banana on the risk of hyperkalemia. Methods : A real experimental study while still adhering to the Covid'19 health protocol. White rats were divided into 4 groups, conditioned by hypertension, then intervened with ramipril and Ambon banana. Blood serum was taken and analyzed using UV spectrophotometry to obtain serum potassium levels. The levels obtained were analyzed using the One Way Anova Test. Results : The mean serum potassium level of the positive control group was 4.93±0.58; negative control 4.13±0.60; normal control 4.76±0.59 and treatment 5.10±0.38. The highest serum potassium level was in the ramipril treatment group together with Ambon banana, but still in the normal range of 3.60–5.50 mmol/L. One Way Anova test results (p = 0.054). (p>0.05) showed no significant difference. Conclusion : There is no specific increase in levels of ramipril concurrently with Ambon banana so it does not have the potential to cause the risk of hyperkalemia.   Keywords : Drug Interaction, Ramipril, Ambon Banana, Serum Potassium, Hyperkalemia